Systematic KMTNet planetary anomaly search. IV. Complete sample of 2019 prime-field. Issue 1 (11th July 2022) - Zang, Weicheng; Yang, Hongjing; Han, Cheongho; Lee, Chung-Uk; Udalski, Andrzej; Gould, Andrew; Mao, Shude; Zhang, Xiangyu; Zhu, Wei; Albrow, Michael D; Chung, Sun-Ju; Hwang, Kyu-Ha; et al.
ABSTRACT: We report the complete statistical planetary sample from the prime fields (Γ ≥ 2 h −1 ) of the 2019 Korea Microlensing Telescope Network (KMTNet) microlensing survey. We develop the optimized KMTNet AnomalyFinder algorithm and apply it to the 2019 KMTNet prime fields. We find a total of 13 homogeneously selected planets and report the analysis of three planetary events, KMT-2019-BLG-(1042, 1552, 2974). The planet–host mass ratios, q, for the three planetary events are 6.34 × 10 −4, 4.89 × 10 −3, and 6.18 × 10 −4, respectively. A Bayesian analysis indicates the three planets are all cold giant planets beyond the snow line of their host stars. The 13 planets are basically uniform in log  q over the range −5.0 < log  q < −1.5. This result suggests that the planets below q break  = 1.7 × 10 −4 proposed by the MOA-II survey may be more common than previously believed. This work is an early component of a large project to determine the KMTNet mass-ratio function, and the whole sample of 2016–2019 KMTNet events should contain about 120 planets.